SCRAMBLE SENTENCE METHOD TO TEACH WRITING DESCRIPTIVE TEXT AT THE EIGHT GRADE STUDENTS OF SMP N 26 PALEMBANG: Scramble sentence method to teach writing descriptive text - Darmawan Budiyanto; Sophia Rahmawati (Journal Of Language Education and Development (JLed), 2019)
The problem of this study is “Is there any significant difference on writing achievement between the eighth grade students of SMP N 26 Palembang who are taught by using scramble sentence method and those who are not?”. This research applied quantitative method namely quasi experimental design and used simple random sampling. The writer used writing rubric to collect data and analyzed the result of test by using paired sample t-test and independent simple t-test. Total number of population was 303 students which is VIII.3 as control group and VIII.I, as experimental group. Based on the result of this study, the mean score in post test score were 73.44 for control group and 76.09 for experimental group. The result of the independent sample t-test shows the value of sig. (2-tailed) was 0.01 < 0.05 at the level of significant 0.05. While, the value of t-obtained was 2.415 higher than the critical value of t-table was 1.665 with degree of freedom 62, can be concluded that the null hypothesis was rejected and the alternative hypothesis was accepted.